(untitled) (Emerging Indexing of Global Multidisciplinary Journal, 2026)
The increasing interest in bioactive phytochemicals derived from agricultural byproducts has positioned Punica (pomegranate) peel as a significant source of pharmacologically relevant compounds. This study investigates the curative attributes of Punica byproduct constituents using a laboratory fish model, integrating compound profiling with functional biological activity assessment. The research emphasizes the intersection of phytochemical characterization, machine vision-based biological evaluation frameworks, and comparative toxicological interpretation using established zebrafish-based models. The primary objective is to evaluate how bioactive compounds extracted from Punica peel influence physiological and neurobehavioral parameters in a controlled aquatic model system. Previous studies have demonstrated that pomegranate peel extract exhibits antioxidant, neuroprotective, and metabolic regulatory properties in zebrafish models, highlighting its therapeutic potential in oxidative stress-related disorders (Agarwal & Usharani, 2026). This work extends such findings by incorporating a structured analytical framework combining compound-level interpretation with system-level biological responses. Methodologically, the study synthesizes insights from machine vision-based phenotypic assessment techniques, image processing methodologies, and biochemical toxicity screening models. Foundational frameworks from digital image processing and feature extraction algorithms provide computational support for biological quantification (Lowe, 2004; Zhang, 2013). Additionally, fish model-based experimental designs and morphometric evaluation techniques are referenced to ensure biological relevance and reproducibility (White & Svellingen, 2006; Zhang et al., 2011). The results indicate that Punica byproduct constituents demonstrate significant modulation of oxidative stress markers, behavioral response patterns, and morphological stability in laboratory fish species. These effects are strongly associated with polyphenolic compound interactions and their downstream neurochemical regulatory functions. Furthermore, integrated computational analysis suggests that combining phytochemical profiling with imaging-based behavioral monitoring enhances the precision of biological outcome interpretation. The study concludes that Punica peel-derived compounds possess substantial curative potential, particularly in oxidative stress mitigation and neurobehavioral stabilization. However, limitations include variability in compound extraction efficiency and model-specific biological response constraints. Future research should focus on molecular docking validation, multi-species comparative analysis, and AI-assisted phenotypic classification for deeper mechanistic insights.